Analisis Profil Pelajaran Pancasila Pada Kartun Riko The Series - Saba Tini, Desi (Mulya Literasi Publishing, 2022)
One of the problems that can be encountered in the field is being picky with friends caused by the weakening of the practice of Pancasila and citizenship education values in the realm of elementary schools. The practice of Pancasila in question is a direct application in the school environment to be used as a personal habituation that can be applied in everyday life. The purpose of this study was to determine the profile analysis of pancasila lessons in riko the series cartoons. This research uses a qualitative approach method. The object of study in this study is the Riko The Series cartoon series video which has 42 episodes. In collecting data for this study is Riko The Series 8th episode. In this study, the data used was the animation of Riko The series in episode 8 and the book or journal related to the research. Data analysis techniques are the process of systematically searching and structuring. Based on the results of the study, it can be concluded that the moral values contained in the animated series Riko The Series episode 8 are better to forgive, namely helping and caring for fellow friends. The relevance of moral values in the animated series Riko The Series episode 8 Better Forgives with socially caring characters